Conhecimento de pessoas com hipertensão e/ou diabetes acerca de sua doença e de suas praticas relacionadas ao estilo de vida na Atenção Primária à Saúde - Santos, Juliana da Silva (2021)
Systemic Arterial Hypertension is important because it is one of the risk factors of several chronic diseases, especially cardiovascular disease, and Diabetes Mellitus is of importance due to its prevalence commonly related to dyslipidemia, arterial hypertension and endothelial dysfunction. Due to epidemiological and demographic transitions in recent decades, there is an increase in the incidence and morbidity and mortality rates of Systemic Arterial Hypertension and Diabetes Mellitus and are also the main cause of hospitalizations by the Unified Health System. For people with hypertension and / or diabetes about their disease and about their lifestyle-related practices, a qualitative descriptive study was conducted. Data collection was performed using the Focal Group (FG) technique, with 16 hypertensive and / or diabetic users attended at primary health care units, from the Family Health Strategy (FHS) of Campina Grande / PB. Data from both focus groups were fully transcribed and submitted to Content Analysis, thematic modality, from which emerged the following thematic categories: 1. Knowledge of people with hypertension and / or diabetes about their disease, 2. Care of the disease, 3. Facilities for taking care of the disease, 4. Difficulties in taking care of the disease, 5. Knowledge of the importance of healthy eating, 6 Knowledge about the importance of physical activity, 7. Weaknesses and Potentialities of drug therapy. It was found that the knowledge of hypertensive and / or diabetic about their chronic condition refers to aspects related to chronicity and complications, treatment, such as undesirable reactions of medication and complex therapeutic regimens, and also about changes in life. Illnesses and the importance of treatment adherence and healthy lifestyles, which makes behavioral changes essential for optimal treatment follow-up. It is hoped that the results may contribute to the expansion of knowledge production that enables the identification of intervention priorities to improve the attention of people with systemic hypertension and / or diabetes mellitus and it is estimated that the results allow the reflection on the chronic conditions in the studied context, providing a debate on lifestyle changes in the general population and particularly among people with Systemic Arterial Hypertension and / or Diabetes Mellitus